2017
DOI: 10.1371/journal.pone.0180152
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different re-warm up activities in football players' performance

Abstract: Warm up routines are commonly used to optimize football performance and prevent injuries. Yet, official pre-match protocols may require players to passively rest for approximately 10 to 15 minutes between the warm up and the beginning of the match. Therefore, the aim of this study was to explore the effect of different re-warm up activities on the physical performance of football players. Twenty-Two Portuguese elite under-19 football players participated in the study conducted during the competitive season. Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 38 publications
3
31
1
2
Order By: Relevance
“…The utilization of heated garments had the best effect size compared with resting in sprint (− 1.45%, d = 2.21) and jump performance (3.13%, d = 1.62). Among all the strategies, only the use of eccentric exercise was detrimental to performance, showing the worst effect on sprint (0.1%; ± 1.3) and jump performance (− 1.8%; ± 2.7) [28].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The utilization of heated garments had the best effect size compared with resting in sprint (− 1.45%, d = 2.21) and jump performance (3.13%, d = 1.62). Among all the strategies, only the use of eccentric exercise was detrimental to performance, showing the worst effect on sprint (0.1%; ± 1.3) and jump performance (− 1.8%; ± 2.7) [28].…”
Section: Resultsmentioning
confidence: 99%
“…However, studies on this topic are scarce and have mostly focused on football. Four studies on the effects of a re-warm-up found that active strategies, for example, 7-8 min of running with an intensity of ~ 70% HR max [65][66][67], as well as a post-activation strategy of four sets of five jumps [28], were better for subsequent performance than the traditional interval rest. However, these results should be interpreted carefully, as one study reported that eccentric exercise could increase the decline in performance and that it should be avoided [28].…”
Section: Half-time Re-warm-upmentioning
confidence: 99%
“…The full-pace exercise (20 and 30 m with COD) and the best CMJ trial were used for data analysis. This warm-up protocol is based on previous studies [12] and the total time taken was 15 min.…”
Section: Testing Proceduresmentioning
confidence: 99%
“…These physiological factors can impair performance during the breaks and the periods of inactivity. Thus, active R-WU activities during the rest period after WU, such as plyometric and repeated change-of-direction exercises, attenuate losses in jump performance and sprint capacity in team sports [12], are also physiologically key factors in rugby.…”
Section: Introductionmentioning
confidence: 99%
“…Protokol pra pertandingan resmi mengharuskan pemain untuk melakukan pemanasan antara 15-30 menit atau bahkan lebih lama lagi dan diakhiri antara 10-15 menit dan awal mulai pertandingan. 20 Pemanasan biasanya dimaksudkan untuk menghasilkan peningkatan suhu otot yang memungkinkan beberapa perubahan internal terjadi, seperti peningkatan aliran darah dan respons metabolisme yang dioptimalkan. Dengan demikian, pemanasan yang ideal harus memungkinkan atlet untuk mencapai kisaran suhu otot yang optimal yang membatasi kelelahan sebanyak mungkin sambil memaksimalkan kinerja.…”
Section: Durasi Pemanasanunclassified